Neuerwerbungen 1971 - 1974 : Kunsthalle zu Kiel. - Jensen, Jens Christian (Kiel : Kunsthalle zu Kiel, 1974)
Meyer, Jobst ; Mields, Rune ; Mortensen, Richard ; Neuenhausen, Siegfried ; Petrick, Wolfgang ; Pfahler, Georg Karl ; Rainer, Arnulf ; Reusch, Erich ; Richter, Gerhard ; Schreib, Werner ; Schult, HA ; Schultze, Bernhard ; Wilding, Ludwig ; Wunderlich, Paul ; etc.
Neuerwerbungen 1971 - 1974, Kunsthalle zu Kiel, 4. August - 6. Oktober '74
boek